2008
DOI: 10.1063/1.2894568
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen vacancies on Schottky contacts to ZnO

Abstract: Ni, Ir, Pd, Pt, and silver oxide Schottky contacts were fabricated on the Zn-polar face of hydrothermally grown, bulk ZnO. A relationship was found between the barrier height of the contact and the free energy of formation of its “metal” oxide. This is consistent with the dominating influence of oxygen vacancies (VO) which tend to pin the ZnO Fermi level close to the VO (+2,0) defect level at approximately 0.7eV below the conduction band minimum. Therefore, a key goal in the fabrication of high quality Schottk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
145
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(160 citation statements)
references
References 21 publications
10
145
1
Order By: Relevance
“…Oxygen plasma can be used to reduce the hydrocarbon and hydroxide accumulation layer on the ZnO surface, remove the nearsurface defects and donors, and also prevent surface chemisorption of oxygen species. 17 Mosbacker et al found that ZnO exposure to oxygen plasma changes the Au contacts on ZnO from ohmic to rectifying contacts, regardless of the surface polarity and the material quality. 4 ZnO nanorod (NR) polarity has no influence on the Au Schottky contacts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxygen plasma can be used to reduce the hydrocarbon and hydroxide accumulation layer on the ZnO surface, remove the nearsurface defects and donors, and also prevent surface chemisorption of oxygen species. 17 Mosbacker et al found that ZnO exposure to oxygen plasma changes the Au contacts on ZnO from ohmic to rectifying contacts, regardless of the surface polarity and the material quality. 4 ZnO nanorod (NR) polarity has no influence on the Au Schottky contacts.…”
Section: Introductionmentioning
confidence: 99%
“…This process is too deep to contribute significantly to the unintentional n-type conductivity of ZnO but is shallow enough to cause the Fermi level pinning at the ZnO interfaces. 17 It has been proposed that the oxygen vacancies strongly influence Schottky barrier formation by pinning the ZnO Fermi level close to the V O (þ2,0) defect level at $0.7 eV below the conduction band minimum. 17 However, good quality Schottky contacts to ZnO have not been found to degrade in terms of performance over time, so V O creation probably occurs simultaneously with the contact formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Metal/ZnO interfaces are essential to all ZnO electronic device applications, yet fabricating high quality and thermally stable rectifying and Ohmic ZnO contacts remains a challenge and their electronic properties have only recently been explored in detail. [2][3][4][5][6][7] Metals on semiconductors seldom obey the Schottky-Mott theory, i.e., their Schottky barrier heights are not proportional to their work functions. 8 Previous ZnO surface studies revealed the importance of surface adsorbates, near-interface native defects, and thermally induced interface chemical interactions at metal/ZnO contacts.…”
mentioning
confidence: 99%
“…6-8, 23, 24 Non-ideal behavior is often attributed to defect states in the band gap of the semiconductor providing other current transport mechanisms such as structural defects, surface contamination, barrier tunneling, or generation recombination in the space charge region and to variations in the interface composition. 25,26 To understand which mechanisms influence the junction behavior, the I-V characteristics of the device are studied in a log-log scale.…”
Section: Resultsmentioning
confidence: 99%